1997
DOI: 10.1128/iai.65.4.1217-1222.1997
|View full text |Cite
|
Sign up to set email alerts
|

Production of interleukin-8 (IL-8) by cultured endothelial cells in response to Borrelia burgdorferi occurs independently of secreted [corrected] IL-1 and tumor necrosis factor alpha and is required for subsequent transendothelial migration of neutrophils

Abstract: Previous studies have shown that Borrelia burgdorferi, the spirochetal agent of Lyme disease, promotes inflammation by stimulating endothelial cells to upregulate adhesion molecules for leukocytes and to produce a soluble agent that is chemotactic for neutrophils. We determined that interleukin-8 (IL-8) was the chemotactic agent for neutrophils present in conditioned media from cultured human umbilical vein endothelial cells stimulated with B. burgdorferi. As few as one spirochete per endothelial cell stimulat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
17
0

Year Published

1998
1998
2024
2024

Publication Types

Select...
4
3

Relationship

0
7

Authors

Journals

citations
Cited by 54 publications
(19 citation statements)
references
References 39 publications
1
17
0
Order By: Relevance
“…In addition, endogenous IL‐8 secreted by activated endothelial cells induces transendothelial neutrophil migration. Burns et al . (1997) have demonstrated that IL‐8 is the major soluble chemoattractant produced by HUVECs exposed to B. burgdorferi .…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In addition, endogenous IL‐8 secreted by activated endothelial cells induces transendothelial neutrophil migration. Burns et al . (1997) have demonstrated that IL‐8 is the major soluble chemoattractant produced by HUVECs exposed to B. burgdorferi .…”
Section: Discussionmentioning
confidence: 99%
“…During the past decade, many investigators have contributed to the understanding of the inflammatory response to Lyme disease ( Schaible et al ., 1994 ; Sellati et al ., 1995 ; 1996; 1998; Wooten et al ., 1996 ; 1998; Burns et al ., 1997 ; Ebnet et al ., 1997 ; Burns and Furie, 1998). The components of innate immunity responding to the infection have been identified, and the integration of these components has been worked out in detail.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Both gelatinolytic bands disappeared when the zymography was performed in the presence of 1 mM 1,10-phenanthroline, a specific MMP inhibitor (not shown). It has been reported that endotoxin is occasionally found in the BSK II medium (Ma and Weis, 1993;Burns et al, 1997), and it could be carried as a contamination by the spirochaetes. To determine whether the MMP-9 induction is due to endotoxin bound on the spirochaete's surface, we tested whether polymyxin B, which binds to endotoxin, could inhibit the MMP-9 induction.…”
Section: Incubation Of Neural Cultures With B Burgdorferimentioning
confidence: 99%
“…The induction of chemokines and adhesion molecule upregulation on both endothelial and infiltrating cells is required for the infiltration of inflammatory cells, such as neutrophils, into tissues (15). Outer-surface components of B. burgdorferi have been documented to upregulate both chemokine and adhesion molecule expression on inflammatory cells (4,5,(12)(13)(14)18). Neutrophil degranulation is induced by stimulation with B. burgdorferi lipoproteins in vitro as well (10).…”
mentioning
confidence: 99%